2021
DOI: 10.1088/1674-4527/21/4/83
|View full text |Cite
|
Sign up to set email alerts
|

The Mg ii absorption line systems in quasar spectra from the Large Sky Area Multi-Object Fiber Spectroscopic Telescope

Abstract: Making use of quasar spectra from LAMOST, in the spectral data around the Mg ii emission lines, research described in this paper has detected 217 Mg ii narrow absorption lines (NALs) with W r λ 2796 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…From the "Unknown" data set in LAMOST DR7, Lu et al (2022) identified 106 new emission line galaxies and 29 new galactic H II regions. Chen et al (2021) penetrated into the Mg II absorption line systems in QSO spectra from LAMOST DR1-5. Chen et al (2023) derived an initial statistical analysis of LAMOST DR9 low resolution QSOs.…”
Section: Introductionmentioning
confidence: 99%
“…From the "Unknown" data set in LAMOST DR7, Lu et al (2022) identified 106 new emission line galaxies and 29 new galactic H II regions. Chen et al (2021) penetrated into the Mg II absorption line systems in QSO spectra from LAMOST DR1-5. Chen et al (2023) derived an initial statistical analysis of LAMOST DR9 low resolution QSOs.…”
Section: Introductionmentioning
confidence: 99%